Desafios da educação ambiental no ensino superior amazônico - VIANA, Janise Maria Monteiro Rodrigues (Universidade de São Paulo, 2023)
The current socio-environmental problem contributes to the emergence of several reflections that highlight the forms of social relations and the environment. This study aims to analyze the status of Environmental Education in undergraduate courses at the Federal University of Pará, University Campus Ananindeua, located in the Amazon region of Pará. To this end, a theoretical and documental research is carried out, based on the curricular prescriptions, pedagogical projects of the courses and subject programs. It is concluded that Environmental Education must occur in an interdisciplinary way, so that there is an approximation between environmental issues, academic technical content and social responsibility.